RANCANG BANGUN SISTEM PENJUALAN DAN PEMESANAN PADA NURCHO TAYLOR JAKARTA BERBASIS WEB (Information Technology and Telematics, 2015)
Abstract Design of Sales System and Reservations in Nurcho Taylor located in Jakarta, at St. Pal Batu 3 RT 14/ RW 11. The former system that applied in Nurcho Taylor is still manual, and it still has a lot of obstacles, one of them is the need of a very long process and complicated. So, it does not running effectively and efficiently. The new system that applied in Nurcho Taylor is considered to facilitate the performance of employers, and customers who wants to order the product online. This sale system and reservation in Nurcho Taylor developed by usingPrototyping system with the use ofPHP and database MySQLprogramming languages. This new system is made to facilitate the management of the data from the customer who order and the transactional data of product ordering. The method of collecting data is filed studies which cover observation, interview with the manager of Nurcho Taylor, andliterature review. Keywords : Sale System,Reservations, Prototyping Method,PHP, MySQL